PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF JIGSAW DALAM MATA PELAJARAN PPKN UNTUK MENINGKATKAN HASIL DAN MINAT BELAJAR SISWA DI SMP NEGERI 7 SINGARAJA - Ida Ayu Kade Wulan Budi Astiti; Yudana , I Made (Jurnal Media Komunikasi Pendidikan Pancasila dan Kewarganegaraan, 2025)
This study aims to examine the impact of implementing the Jigsaw cooperative learning model on improving student learning outcomes and interest in Pancasila and Civic Education (PPKn) subjects. This study was motivated by the continued dominance of conventional learning methods, which have resulted in low student participation, interest, and understanding of PPKn material. To address this problem, the Jigsaw cooperative learning model was applied, which emphasizes group cooperation, individual responsibility, and active interaction among students in the learning process. This study used a quasi-experimental method with a posttest-only control group design, where the research subjects were eighth-grade students at SMP Negeri 7 Singaraja in the 2024/2025 academic year. Data collection techniques were carried out through tests to measure learning outcomes and questionnaires to measure students' interest in learning. Based on the results of data analysis, a significant increase was found in student learning outcomes and interest in learning after the application of this learning method in several relevant studies. Keywords: jigsaw cooperative learning model, learning outcomes, interest in learning, civics education